2012
DOI: 10.1111/j.1460-9568.2012.08259.x
|View full text |Cite|
|
Sign up to set email alerts
|

Syntaxin 1 is required for DCC/Netrin‐1‐dependent chemoattraction of migrating neurons from the lower rhombic lip

Abstract: Directed cell migration and axonal guidance are essential steps in neural development that share many molecular mechanisms. The guidance of developing axons and migrating neurons is likely to depend on the precise control of plasmalemma turnover in selected regions of leading edges and growth cones, respectively. Previous results provided evidence of a signaling mechanism that couples chemotropic deleted in colorectal cancer (DCC)/Netrin-1 axonal guidance and exocytosis through Syntaxin1(Sytx1)/TI-VAMP SNARE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 77 publications
(98 reference statements)
5
38
0
Order By: Relevance
“…Pioneering work in budding yeast and neurons identified genes involved in secretion, including the Soluble N-ethylmaleimide-sensitive factor Attachment protein Receptors (SNARE) proteins, which comprise the SNARE complex, the minimal protein requirement for fusion of two lipid bilayers (Cotrufo et al, 2012; Hayashi et al, 1994; McMahon and Südhof, 1995; Novick et al, 1980; Söllner et al, 1993a). …”
Section: Exocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering work in budding yeast and neurons identified genes involved in secretion, including the Soluble N-ethylmaleimide-sensitive factor Attachment protein Receptors (SNARE) proteins, which comprise the SNARE complex, the minimal protein requirement for fusion of two lipid bilayers (Cotrufo et al, 2012; Hayashi et al, 1994; McMahon and Südhof, 1995; Novick et al, 1980; Söllner et al, 1993a). …”
Section: Exocytosismentioning
confidence: 99%
“…As is the case with deletion of SNAP25 , genetic deletion of the syntaxin1A gene ( STX1A ) is not associated with gross neuroanatomical differences (Fujiwara, 2006). In contrast, treatment with botulinum neurotoxin C (BoNTC1), which cleaves both SNAP25 and syntaxin1, causes growth cone collapse and inhibited neurite outgrowth in chick DRGs, and blocks biased neurite outgrowth toward an asymmetric netrin-1 source in mouse hippocampal explants (Cotrufo et al, 2012; Hayashi et al, 1994; Igarashi, 1996). Since treatment with BoNTA, which cleaves SNAP25 and leaves syntaxin intact, does not recapitulate these results, syntaxin1 is likely required for preferential outgrowth toward netrin, whereas another SNAP family member appears to compensate for loss of SNAP25 function.…”
Section: Exocytosismentioning
confidence: 99%
“…This interaction is required for UNC-6/Netrin-dependent migration of axons (Cotrufo et al 2012). Localized insertion of membrane at sites of activation of guidance receptors is thought to be the key function of this interaction (Tojima et al 2011;Tojima and Kamiguchi 2015).…”
Section: Discussionmentioning
confidence: 99%
“…unc-64 encodes the nematode homolog of Syntaxin, a SNARE component involved in the fusion of synaptic vesicles (Saifee et al 1998). Recently it has been shown that Syntaxin1 binds to the guidance receptor DCC in the growth cone, where it is required for chemoattraction of migrating axons to the guidance cue Netrin (Cotrufo et al 2012). We wanted to test whether unc-31 and unc-64 mutants have AVG axon guidance defects similar to those seen in aex-3.…”
Section: Aex-3 Mutant Animals Show Nid-1-dependent Avg Axon Navigatiomentioning
confidence: 99%
See 1 more Smart Citation